Cardiac Fibrosis: Only from Resident Cardiac Fibroblasts? - Sukhbaatar, Pagmadulam; Khorloo, Chingerel; Nyamsuren, Bat-Erdene; Vanchin, Byambasuren (Central Asian Journal of Medical Sciences, 2019)
No abstract in English